Expression and clinical significance of 3 kinds of circular RNA in systemic lupus erythematosus - GUO Junkai1; ZHAO Xingwang; NI Bing; YOU Yi (Di-san junyi daxue xuebao, 2020)
Objective To explore the expression and significance of 3 circular RNAs (circRNA), that is, circADCY9, circGARS and circMCTP2, in the patients with systemic lupus erythematosus (SLE), so as to provide new ideas and directions for its clinical diagnosis and treatment. Methods Peripheral blood mononuclear cells (PBMCs) were extracted from the SLE patients (n=35) and healthy volunteers (n=25, control group). The expression levels of above 3 circRNAs were detected by real-time quantitative PCR (RT-qPCR), and their correlations with SLE Disease Activity Index (SLEDAI) were analyzed. The diagnostic value of the 3 circRNAs was evaluated by receiver operating characteristic (ROC) curve. Their stability and tolerance were detected using ribonuclease R (RNaseR) treatment, and the stability of circADCY9 was further verified by PCR analysis. Results ① The levels of circADCY9 and circGARS were up-regulated, while that of circMCTP2 was down-regulated (All P values were < 0.000 1) in the SLE patients than the healthy volunteers. ② In SLE patients, the expression levels of circADCY9 and circGARS were positively correlated with the score of SLEDAI, and negatively with the level of complement C3. By contrast, the circMCTP2 level was negatively correlated with SLEDAI score and positively with complement C3 level. ③ The area under the curve (AUC) for circADCY9, circGARS and circMCTP2 were 0.850 0, 0.826 7 and 0.895 6, respectively. ④ The expression levels of the 3 circRNAs remained steady before and after RNaseR treatment, and the result of PCR showed that the tolerance of circADCY9 to RNaseR was better than that of ADCY9 mRNA. Conclusion The expression of circADCY9, circGARS and circMCTP2 is significantly abnormal in the PBMCs of SLE patients, and shows good stability, which is correlated with the activity of SLE.